The handmaiden [videorecording (DVD)] - Pak, Ch'an-uk, 1963-; Kim, Min-hŭi, 1982-; Ha, Chŏng-u, 1979-; Cho, Chin-ung, 1976-; Waters, Sarah, 1966- (Sony Pictures Home Entertainment, 2017)
A Korean woman who is hired as handmaiden to a young Japanese lady is secretly plotting with a conman to defraud her of her large inheritance.